Permainan Tiga Dimensi (3d) Untuk Pengenalan Makanan Alergen Telur, Kacang Dan Susu Serta Tahap Intervensi Diet Pada Anak - Stella Joice Luhulima; Anang Kukuh Adisusilo; Nia Saurina (Informatics Engineering Department-UWKS, 2017)
In the past few years, the incidence of allergies continues to rise, both domestically and abroad. World Allergy Organization (WAO) said 22% of world population suffers from allergies and continues to increase every year. Food allergy is a condition caused by the reaction of IgE against food ingredients (chemicals). Therefore, prevention arrival of allergy symptoms it is recommended in order the patient does not get any of allergic symptoms. It would be better to handle and to fight allergies and need to be done to their diets for immune therapy or we used to call it the Intervention Diet which is undertaken gradually to reduce the body's reaction to certain allergens. The design of this 3D game using Unity. In this research generated knowledge information about allergies, healthy foods which is good to avoid food allergy symptoms also any of food which can cause allergic symptoms and proper diet treatment for immune therapies to reduce body's reaction to certain allergens. The results of this research are making a game about the symptoms of allergic disease, health body, foods, which it should be avoided by children, so their parents will get the information how to separating foods containing allergens. As well as the results of this testing research, this applications showed a percentage, more than 75% of children are interested to use this game as a medium of learning about food allergens.